SIGNIFICANCE OF LEARNING ORGANISATION IN HOSPITALITY AND RETAIL INDUSTRIES – IMPLICATIONS TO HUMAN RESOURCE MANAGEMENT - Ka Shing, LAU (International Journal of Psychosocial Rehabilitation, 2021)
This paper aimed to review previous and recent researches of learning organisation, and organisational learning in hospitality and retail industries, as well as the implications to human resource management, in regard to their roles and strategies to changes, learning environment, and organisational competitiveness. Supporting by the present state of understanding on the topic, it tried to demonstrate on a theoretical basis and further studied in-depth on the research trend of learning organisation related from human resource view. This paper can be a foundation possibly for future development or extension of a new research relating to the topic of learning organisation, and further exploration of relevant new findings. It can potentially contribute to the area of organisational learning with the particular industries.